Autopsy ebook - Cornwell, Patricia (Kay Scarpetta, 2021)
New York Times Bestseller In this relaunch of the electrifying, landmark #1 bestselling thriller series, chief medical examiner Dr. Kay Scarpetta hunts those responsible for two wildly divergent and chilling murders. Forensic pathologist Dr. Kay Scarpetta has come almost full circle, returning to Virginia, the state where she launched her storied career, as the chief medical examiner. Finding herself the new girl in town once again after being away for many years, she's inherited both an overbearing secretary and a legacy of neglect and potential corruption. She and her husband, Benton Wesley, now a forensic psychologist with the U.S. Secret Service, have relocated to Old Town Alexandria, where she's headquartered five miles from the Pentagon in a post-pandemic world that's been torn apart by civil and political unrest. After just weeks on the job, she's called to a scene by railroad tracks—a woman's body has been shockingly displayed, her throat cut down to the spine—and as Scarpetta begins to follow the trail, it leads unnervingly close to her own historic neighborhood. At the same time, a catastrophe occurs in a top secret laboratory in outer space, endangering at least two scientists aboard. Appointed to the highly classified Doomsday Commission that specializes in sensitive national security cases, Scarpetta is summoned to the White House and tasked with finding out exactly what happened. But even as she remotely works the first potential crime scene in space, an apparent serial killer strikes again very close to home. This latest novel in the groundbreaking Kay Scarpetta series captivates readers with the shocking twists, high-wire tension, and forensic detail that Patricia Cornwell is famous for, proving once again why she's the world's #1 bestselling crime writer.